Social Control, Martial Conformity, and Community Entanglement: The Varied Beat of the Hamilton Police, 1895-1920 - Weaver, John (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1990)
The aim of this inquiry into the composition and conduct of the Hamilton police force in the early twentieth century is to indicate the merit of certain historical criticisms of policing while modifying them with evidence about inefficiency and inconcistency in the performance of social control measures as well as evidence of positive activities in the area of social services. The city police were called upon to enforce moral order by religious and elite groups; they were asked to be domestic missionaries. However, their working-class origins and the temptations encountered on the beat made them inconsistent if not indefferent enforcers of morality. When required to protect private property during strikes, they did so but lacked the resources to be an effective complement to the strike-breaking measures of large concerns. Although their very presence may have deterred crime, their actual crime prevention and detection activities were ineffectual. They performed other urban functions: enforcing bylaws and statutes that dealt with everything from the regulation of trade to public health, looking for missing persons, returning lost children, operating a hostel for the homeless, and dealing with assorted situations of potential and actual violence. The police had the most varied and sensitive duties of all urban-service professionals, but were the least well trained and educated.